Analysis of the Effectiveness of Organization-Based Learning on Nursing Performance at Regional General Hospital - Daniel Bagus Setyawan; Haris Supratno; Erny Roesminingsih (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Improving services in hospitals is related to the effectiveness of the performance of health workers, especially nurses. Nurses are also the health workers who most often and longest interact with patients. Hospitals have well received the concept of organization-based learning as a health institution. Organizational-based learning is necessary for the development of employees and the institution itself. This study analyzes the effectiveness of implementing organization-based learning on nurses' performance at Regional General Hospital Dr. WahidinSudiroHusodoMojokerto City. Method: This qualitative research uses primary and secondary data. Data collection techniques are through observation and interviews. The selection of informants in this study was carried out using the total sampling method. Results: The results showed that organization-based learning improves nurses' performance in inpatient service. Novelty: Organizational-based learning can be applied in hospitals to improve nursing performance in providing services. The head of the room must also be a good manager when implementing this program.